Transformasi Pertanian: Memanfaatkan Limbah Kulit Bawang Merah Sebagai Pestisida Ramah Lingkungan dan Pupuk Organik yang Aman Bagi Petani - Derita Ramai Durubanua; Ivan Rivaldo Sihombing; Putri Rahmadani; Meilinda Suriani Harefa; Syukrie Hidayat (Pusat Riset dan Inovasi Nasional, 2024)
Problems that cannot be separated from the agricultural sector, especially in Kec. Percut Sei Tuan, Kab. Deli Serdang is the use of chemical pesticides in agriculture. The use of pesticides in agriculture can have positive and negative consequences for the environment and also the health of farmers. The abundance of onion skin waste is another way that can be optimized for its use as a standard ingredient for making organic pesticides. The aim of this research is to transform the use of chemical pesticides into organic pesticides. The practical method used in this journal is qualitative. Making pesticides from onion skin waste can be used to control pest attacks and rice plant diseases. Using onion skin waste as an environmentally friendly pesticide is a more sustainable alternative and has a smaller negative impact on the environment compared to using chemical pesticides.